Human Side of Collaborative Partnerships: A Microfoundational Perspective. (April 2017) - Liu, Yipeng; Sarala, Riikka M.; Xing, Yijun; Cooper, Sir Cary L.
The research on collaborative partnerships has accumulated a vast body of knowledge, which has assisted us with comprehending several complex organizational phenomena, including mergers and acquisitions, strategic alliances, joint ventures, and entrepreneurial partnerships. Yet, the existing studies have not paid sufficient attention to the human side factors. We join the current conversation within the microfoundations perspective of management and organization studies by suggesting that investigating the human side factors as the microfoundations of collaborative partnerships can advance our collective understanding of the phenomena in important ways. This article has three general objectives. First, we show that collaborative partnerships have been a long-standing issue in management and organization studies and provide an overview of the puzzles that informed and motivated this special issue. Second, we highlight the key insights and contributions of the articles included in this special issue by reviewing their theoretical underpinnings, methodological approaches, and findings. Finally, we outline a future research agenda on the human side of collaborative partnerships that can help advance management and organization studies.